THE ROLE OF PSYCHOLOGY WHILE TEACHING ENGLISH IN PRIMARY SCHOOLS - Rustamova, Adash Eshankulovna; Eshankulova, Sarvinoz Safarovna (INTERNATIONAL CONFERENCES, 2023)
It is difficult to overestimate the meaning of a foreign language for modern society as it influences. Directly all the main life aspects in the development of every country. It is common phenomenon and indisputable fact is that the role of psychology while teaching foreign languages in primary schools are significant.